2006
DOI: 10.1111/j.1365-2966.2005.09930.x
|View full text |Cite
|
Sign up to set email alerts
|

First estimates of the fundamental parameters of the relatively bright Galactic open cluster NGC 5288

Abstract: In this paper we present charge‐coupled device (CCD) images in the Johnson B and V and Kron–Cousins I passbands for the previously unstudied open cluster NGC 5288. The sample consists of 15 688 stars reaching down to V∼ 20.5. The cluster appears to have a relatively small but conspicuous nucleus and a low‐density extended coronal region. Star counts carried out in 25 × 25 pixel2 boxes distributed throughout the whole observed field allowed us to estimate the angular core and corona radii as ∼1.3 and 6.3 arcmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…We compared the cluster density profile with those of other clusters observed using both the same CCD and the same telescope, having previously normalized the respective field star densities. We found that NGC 2489 has an intermediate star density, like NGC 2194 (Piatti et al 2003a), NGC 2324 (Piatti et al 2004b), Tombaugh 1 (Piatti, Clariá & Ahumada 2004c) and Lyngå 11 (Piatti et al 2006a), which are between the highest density clusters NGC 6318 (Piatti, Clariá & Ahumada 2005) and Tr 5 (Piatti, Clariá & Ahumada 2004a) and the lowest density cluster NGC 5288 (Piatti et al 2006b). Regarding the shape of the NGC 2489 density profile, it compares well at the core with those of clusters of intermediate star densities, but shows additionally a corona not so extended as that of NGC 5288.…”
Section: Data Handlingmentioning
confidence: 73%
See 1 more Smart Citation
“…We compared the cluster density profile with those of other clusters observed using both the same CCD and the same telescope, having previously normalized the respective field star densities. We found that NGC 2489 has an intermediate star density, like NGC 2194 (Piatti et al 2003a), NGC 2324 (Piatti et al 2004b), Tombaugh 1 (Piatti, Clariá & Ahumada 2004c) and Lyngå 11 (Piatti et al 2006a), which are between the highest density clusters NGC 6318 (Piatti, Clariá & Ahumada 2005) and Tr 5 (Piatti, Clariá & Ahumada 2004a) and the lowest density cluster NGC 5288 (Piatti et al 2006b). Regarding the shape of the NGC 2489 density profile, it compares well at the core with those of clusters of intermediate star densities, but shows additionally a corona not so extended as that of NGC 5288.…”
Section: Data Handlingmentioning
confidence: 73%
“…In some cases, BVI photometry proved to be a valuable tool for obtaining the fundamental parameters of star clusters, since information on cluster membership, distance, reddening and age is obtained through the analysis of ( V , B − V ) and ( V , V − I ) colour–magnitude diagrams (CMDs; see e.g. Piatti, Clariá & Ahumada 2006a,b). In other cases, CCD photometric data obtained with the Johnson V and Kron–Cousins I filters were supplemented with CCD or photoelectric Washington photometric data to determine the cluster fundamental parameters and, mainly, to estimate cluster metal content (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We compared the stellar density radial profile of NGC 2236 with those of other open clusters we observed using both the same CCD and telescope: NGC 2194 (Piatti et al 2003a); Tr 5 (Piatti et al 2004a); NGC 2324 (Piatti et al 2004b); Tombaugh 1 (Piatti et al 2004c); NGC 6318 (Piatti, Clariá & Ahumada 2005); Lyngå 11 (Piatti, Clariá & Ahumada 2006a); NGC 5288 (Piatti, Clariá & Ahumada 2006b) and NGC 2489 (Piatti et al 2007). We previously normalized these cluster profiles to the distance and field star density of NGC 2236, and expressed the stellar densities in units of number of stars per square parsec.…”
Section: Structural Cluster Featuresmentioning
confidence: 99%
“…We have already reported E-mail: andres@iafe.uba.ar (AEP); claria@oac.uncor.edu (JJC); aahu-mada@eso.org (AVA) results on several relatively young (e.g. Piatti, Clariá & Ahumada 2006), intermediate-age (e.g. Piatti, Clariá & Ahumada 2004a) and old (e.g.…”
Section: Introductionmentioning
confidence: 99%